2011
DOI: 10.1371/journal.pcbi.1002266
|View full text |Cite
|
Sign up to set email alerts
|

Representational Switching by Dynamical Reorganization of Attractor Structure in a Network Model of the Prefrontal Cortex

Abstract: The prefrontal cortex (PFC) plays a crucial role in flexible cognitive behavior by representing task relevant information with its working memory. The working memory with sustained neural activity is described as a neural dynamical system composed of multiple attractors, each attractor of which corresponds to an active state of a cell assembly, representing a fragment of information. Recent studies have revealed that the PFC not only represents multiple sets of information but also switches multiple representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
3
1

Relationship

6
4

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…Then, Torres and Marro generated a detailed phase diagram embedding many patterns associated with stochastic resonance, such that multiple noise levels are well responsible for optimizing input signals (Torres and Marro, 2015). Additionally, it has been reported that the combination of depression and facilitation synapses contributes to flexible information representation, from the viewpoint of both data analysis and mathematical modeling (Katori et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Then, Torres and Marro generated a detailed phase diagram embedding many patterns associated with stochastic resonance, such that multiple noise levels are well responsible for optimizing input signals (Torres and Marro, 2015). Additionally, it has been reported that the combination of depression and facilitation synapses contributes to flexible information representation, from the viewpoint of both data analysis and mathematical modeling (Katori et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…8) Furthermore, it has been suggested that in a network with both depression and facilitation synapses, changes in the efficacy of dynamic synapses reorganize the effective network structure, thereby contributing to flexible information representation in the brain. 9) Although stochastic neural networks with facilitation synapses have been studied, 10) a comprehensive understanding of the dynamics of neural networks with dynamic synapses has not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…2). We also analyzed the fluctuations in activity or firing variability of the representational shift neurons (see Methods) [8]. Our preliminary results indicated that the firing variability increased prior to the representational shift.…”
Section: Kazuhiro Sakamotomentioning
confidence: 99%